2018
DOI: 10.1111/tra.12563
|View full text |Cite
|
Sign up to set email alerts
|

The Sla1 adaptor‐clathrin interaction regulates coat formation and progression of endocytosis

Abstract: Clathrin-mediated endocytosis is a fundamental transport pathway that depends on numerous protein-protein interactions. Testing the importance of the adaptor protein-clathrin interaction for coat formation and progression of endocytosis in vivo has been difficult due to experimental constrains. Here, we addressed this question using the yeast clathrin adaptor Sla1, which is unique in showing a cargo endocytosis defect upon substitution of 3 amino acids in its clathrin-binding motif (sla1 ) that disrupt clathri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Sla1 compartmentalizes into foci at internalization sites on the plasma membrane where it is present until vesicles are fully internalized (Fig. 4C ); its deletion was shown to alter endocytosis dynamics 25 27 . The shuffling of Sla1 SH3s alters PPIs with partners involved in different phases of endocytosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sla1 compartmentalizes into foci at internalization sites on the plasma membrane where it is present until vesicles are fully internalized (Fig. 4C ); its deletion was shown to alter endocytosis dynamics 25 27 . The shuffling of Sla1 SH3s alters PPIs with partners involved in different phases of endocytosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During clathrin-mediated endocytosis, Sla1 is an adaptor linking cargos to clathrin and recruits members of the actin machinery via SH3-dependent PPIs (Fig. 4C ) 25 , 26 . Sla1 compartmentalizes into foci at internalization sites on the plasma membrane where it is present until vesicles are fully internalized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of light-activated TL2 on endocytosis, we followed the cortical dynamics of the GFPtagged coat-associated protein Sla1-GFP. The yeast clathrin adaptor Sla1 is a component of the clathrin coat, whose spatiotemporal dynamics at endocytic sites has been well-characterized 12,13,33 . Spheroplasts of S. cerevisiae expressing Sla1-GFP were treated with either pre-activated TL2 (380 nm) or with vehicle, and cortical patches were live-imaged after 30 minutes incubation.…”
Section: Resultsmentioning
confidence: 99%
“…During this process, vesicles are fully internalized following scission, before complex disassembly. It was previously reported that Sla1 deletion results in altered endocytosis dynamics and defective actin polymerisation (Holtzman, Yang and Drubin, 1993;Kaksonen, Toret and Drubin, 2005;Feliciano and Di Pietro, 2012;Tolsma, Cuevas and Di Pietro, 2018) . We found that Sla1 SH3 shuffling alters its interaction with partners that are themselves associated with different phases of endocytosis, such as clathrin (Chc1), Las17, Pan1, End3 and subunits of the Arp2/3 complex (ARC proteins) ( Figure 5C).…”
Section: Sh3 Domain Positions In Multi-sh3 Proteins Affect Their Ppismentioning
confidence: 97%
“…We extended these analyses by directly examining at the single-cell level Sla1's specific function in clathrin-mediated endocytosis ( Figure 5B) (Feliciano and Di Pietro, 2012;Mund et al , 2018;Tolsma, Cuevas and Di Pietro, 2018;Manenschijn et al , 2019) . During endocytosis, Sla1 plays a central role as an adaptor protein linking cargos to clathrin, in addition to participating in the recruitment of the actin machinery to internalization sites via SH3-dependent PPIs ( Figure 5B) (Feliciano and Di Pietro, 2012;Tolsma, Cuevas and Di Pietro, 2018) . Sla1 appears as compartmentalized into foci at the plasma membrane where it is present until cell membrane invagination is complete.…”
Section: Sh3 Domain Positions In Multi-sh3 Proteins Affect Their Ppismentioning
confidence: 99%